The treatment of a Morel-Lavallée lesion of the thigh with incision and drainage along with tissue debridement and a surgically placed drain: A case report and literature review - Hu, Minhua; Chen, Junbang; Ma, Luyao; Huang, Feng; Cai, Qunbin (Frontiers in Surgery, 2023)
Background: Morel-Lavalle lesion （MLL） is a rare closed degloving injury that usually occurs around the hips and is associated with pelvic fractures after high-energy trauma, which is commonly overshadowed by other severe posttraumatic manifestations. Isolated MLL, mostly caused by low-energy violence, is few rare. Thus, the rates of misdiagnosis and missed diagnosis are often high. In this case report and literature review, we review the pathophysiology, clinical manifestations, imaging data, and treatment of this lesion, to increase awareness of this rare disease. Case report: We experienced a case of isolated MLL in the right thigh caused by trauma that was missed diagnosis at the initial visit and at the return visit with a significant sign of a mass on MRI. Given the size of the lesion, open debridement and irrigation were adopted to treat the lesion, and the patient recovered well post-operatively. Conclusion: Young surgeons should pay attention to MLL with sufficient recognization to avoid missed diagnosis and misdiagnosis. Comprehensive physical examination and imaging data play an important role in the diagnosis of MLL. In the early stages of this injury, a detailed history review, combined with physical examination and MRI can reduce the rate of missed diagnosis and misdiagnosis. The choice of therapeutic scheme depends on the size and severity of the lesion. For an isolated MLL, compared to conservative treatments, we believe that incision and drainage along with tissue debridement and surgically placed drain will reduce the rate of infection and recurrence.